Development and validation of the Protective Gambling Beliefs Scale (PGBS). Issue 1 (2nd January 2019) - Armstrong, Tess; Rockloff, Matthew; Browne, Matthew; Blaszczynski, Alexander
ABSTRACT: This article aimed to develop and validate a measure of protective beliefs – distinct from the absence of erroneous beliefs – that may be associated with resistance to gambling problems. Study 1 was designed to determine the reliability and content validity of a preliminary set of protective belief items. Participants (N = 1479, 813 males) also completed the Problem Gambling Severity Index (PGSI). Most items were associated with reduced risk of problems; however, items relating to an awareness of gambling harm, and preparedness to lose money were positively correlated with gambling problems and were therefore not demonstrably protective. Study 2 sought to reduce scale size and assess the scale's ability to predict risk of gambling problems. Participants (N = 1168, 625 males) completed belief items, the PGSI, and measures of gambling consumption and cognitive distortions. Results showed that endorsement of protective beliefs was negatively correlated with PGSI, gambling consumption and cognitive distortions, and predicted PGSI above that of cognitive distortions. Findings suggest that the Protective Gambling Beliefs Scale (PGBS) offers a unique tool for understanding resistance to the development of gambling problems. Future research should focus on exploring whether protective beliefs can diminish the likelihood of the onset of problem gambling.